In utero exposure to bisphenols and asthma, wheeze, and lung function in school-age children: a prospective meta-analysis of 8 European birth cohorts - Abellan, Alicia; Mensink-Bout, Sara M.; Garcia-Esteban, Raquel; Beneito, Andrea; Chatzi, Leda; Duarte-Salles, Talita; Fernandez, Mariana F.; Garcia-Aymerich, Judith; Granum, Berit; Iñiguez, Carmen; Jaddoe, Vincent W.V.; Kannan, Kurunthachalam; et al. (Environment international, 2022)
•In utero exposure to BPA was prevalent from 1999 to 2010.•In utero exposure to BPA may increase the risk of asthma and wheeze among school-age girls.•No evidence of an association with lung function at school-age nor wheezing patterns across childhood. In utero exposure to bisphenols, widely used in consumer products, may alter lung development and increase the risk of respiratory morbidity in the offspring. However, evidence is scarce and mostly focused on bisphenol A (BPA) only. To examine the associations of in utero exposure to BPA, bisphenol F (BPF), and bisphenol S (BPS) with asthma, wheeze, and lung function in school-age children, and whether these associations differ by sex. We included 3,007 mother–child pairs from eight European birth cohorts. Bisphenol concentrations were determined in maternal urine samples collected during pregnancy (1999–2010). Between 7 and 11 years of age, current asthma and wheeze were assessed from questionnaires and lung function by spirometry. Wheezing patterns were constructed from questionnaires from early to mid-childhood. We performed adjusted random-effects meta-analysis on individual participant data. Exposure to BPA was prevalent with 90% of maternal samples containing concentrations above detection limits. BPF and BPS were found in 27% and 49% of samples. In utero exposure to BPA was associated with higher odds of current asthma (OR = 1.13, 95% CI = 1.01, 1.27) and wheeze (OR = 1.14, 95% CI = 1.01, 1.30) (p-interaction sex = 0.01) among girls, but not with wheezing patterns nor lung function neither in overall nor among boys. We observed inconsistent associations of BPF and BPS with the respiratory outcomes assessed in overall and sex-stratified analyses. This study suggests that in utero BPA exposure may be associated with higher odds of asthma and wheeze among school-age girls.